A molecular study of Mycoplasma gallisepticum field isolates from poultry in southern Africa - Moretti, Serena Angela (University of the Free State, 2012)
Mycoplasma gallisepticum (MG) is an economically important pathogen of poultry worldwide, causing chronic respiratory disease in both chickens and turkeys. Little research has been done to characterize the MG field strains present in southern Africa. Field evidence however, suggested breaks in the vaccinations against MG, despite the proper cold chain and correct administration. Molecular methods were used to screen various poultry farms in South Africa and Zimbabwe for MG. Isolates were further characterized by gene-targeted sequencing (GTS). Portions of the cytadhesin pvpA, gapA, mgc2 genes and the uncharacterized surface lipoprotein gene designated MGA_0319 were sequenced and analysed. Three MG strains were identified in this study: a Ts-11-like strain; a strain showing closest percentage identity to the atypical MG RV-2 strain found in Israel, however with the lack of a large deletion within the pvpA region; and lastly an isolate from Zimbabwe, likely to be a novel MG strain. The latter contained a unique, large, in-frame nucleotide insertion in the mgc2 gene. Antigenically-significant variation (determined in silico) within the membrane surface proteins of this isolate was found compared to the MG Rlow strain used as an inactive vaccine on the poultry farm. It is thus postulated that by MG altering its antigenic profile, it allows effective avoidance of immune recognition and antibodies produced as a result of vaccination with inactivated and possibly live MG vaccines. Further research is however needed to substantiate this claim.

Mycoplasma gallisepticum (MG) is 'n ekonomies belangrike patogeen van pluimvee wêreldwyd, wat chroniese respiratoriese siekte in beide hoenders en kalkoene veroorsaak. Min navorsing is al gedoen om die MG veld stamme wat teenwoordig is in Suider-Afrika te karakteriseer. Ten spyte van die behoorlike koue ketting en korrekte administrasie was daar in die veld bewys dat breke in inentings teen MG wel voorkom. Molekulêre metodes was gebruik om verskeie pluimvee plase in Suid-Afrika en Zimbabwe te ondersoek vir die teenwoordigheid van MG. Isolate was verder gekarakteriseer deur geen geteikende volgordebepalings (GTS). Die volgorde van gedeeltes van die cytadhesin pvpA, gapA, mgc2 gene en die nie gekarakteriseerde oppervlak-lipoproteïen geen genoem MGA_0319 was bepaal en ontleed. Drie MG stamme was in hierdie studie geïdentifiseer: 'n Ts-11-agtige stam, 'n stam met die naaste persentasie identiteit aan die a-tipiese MG RV-2 stam gevind in Israel, maar met 'n gebrek aan die groot delesie in die pvpA streek, en laastens 'n isolaat van Zimbabwe, waarskynlik 'n novel MG stam. Laasgenoemde het 'n unieke, groot inraam nukleotied invoeging in die mgc2 geen. Antigenies-beduidende variasie (soos bepaal in silico) binne die membraan proteïene oppervlak van hierdie isolaat was gevind in vergelyking met die MG Rlow stam wat gebruik was as 'n onaktiewe entstof op die pluimvee plaas. Dit is dus gepostuleer dat die veranderinge wat MG aan sy antigeniese profiel ondergaan het dit effektief van immuun erkenning vermy asook van die teenliggaampies wat as gevolg van inenting met geïnaktiveerde en moontlik lewendige MG entstowwe geproduseer word. Verdere navorsing is egter nodig om hierdie stelling te staaf.
Dissertation (M.Sc. (Microbial, Biochemical and Food Biotechnology))--University of the Free State, 2012
Keywords: Mycoplasma gallisepticum -- Molecular aspects; Mycoplasma diseases in animals; Poultry -- Diseases; Mycoplasma gallisepticum; RV-2 strain; Gene-targeted sequencing (GTS); Epidemiology; Antigenicity; Mgc2; 16S-23S intergenic spacer region; PvpA